2021
DOI: 10.1292/jvms.21-0051
|View full text |Cite
|
Sign up to set email alerts
|

Serum iron concentration is candidate inflammatory marker for respiratory diseases in beef cows

Abstract: We hypothesized that the serum iron (Fe) concentration in cows with respiratory diseases is a satisfactory substitute for major inflammatory markers such as haptoglobin (HPT) and serum amyloid A (SAA). Twenty Japanese Black cows aged 279.6 ± 120.0 days were enrolled, and divided into respiratory diseases and control groups based on the presence of clinical findings of respiratory diseases. As a result, area under the receiver operating characteristic curves for plasma HPT, SAA and serum Fe concentrations for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Regarding bovine, Shimamori et al observed a decrease in serum Fe concentrations and an increase in SAA in calves after dehorning, and serum Fe was also negatively correlated with SAA and HPT in adult cattle [18]. This result is supported by Tsukano's nding that serum Fe, as well as HPT and SAA, exhibited diagnostic potential for respiratory disease in Japanese black cows [17]. In the current study, serum Fe concentrations were found to be negatively correlated with SAA in cattle.…”
Section: The Clinical Application Of Trace Elementsmentioning
confidence: 86%
See 2 more Smart Citations
“…Regarding bovine, Shimamori et al observed a decrease in serum Fe concentrations and an increase in SAA in calves after dehorning, and serum Fe was also negatively correlated with SAA and HPT in adult cattle [18]. This result is supported by Tsukano's nding that serum Fe, as well as HPT and SAA, exhibited diagnostic potential for respiratory disease in Japanese black cows [17]. In the current study, serum Fe concentrations were found to be negatively correlated with SAA in cattle.…”
Section: The Clinical Application Of Trace Elementsmentioning
confidence: 86%
“…Therefore, Fe is likely to be associated with an in ammatory response [16]. In addition, Serum Fe concentrations were signi cantly decreased in beef cattle with respiratory disease and in calves during the rst 24 hours after dehorning [17,18]. Moreover, the measurement of the serum Fe concentration is inexpensive, does not require special equipment, and can be performed simultaneously with other biochemical tests, making it less time-consuming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron is a negative APR that has shown a good ability to discriminate between health and inflammation in domesticated animals like horses and cattle. [72][73][74][75] Serum iron has been measured in several nondomesticated mammals; results from studies that included iron measurement in the context of inflammatory disease can be found in Table 4. 23,33,34,36,76 Serum iron measurement is available on most automated wet chemistry systems, using the spectrophotometric ferrozine zinc method.…”
Section: Ironmentioning
confidence: 99%
“…13,14 In veterinary medicine, low serum iron has been documented in various animal species with inflammatory diseases, and serum iron has been shown to be a good biomarker for inflammation in horses, cattle, and white rhinoceros. 4,[17][18][19][20][21] African elephants are endangered, with increasing human populations, habitat loss, unsustainable harvesting of ivory and human-elephant conflict all considered significant risks to species survival. 22,23 Optimized diagnostic testing and treatment of diseased or wounded elephants is important as part of a multifaceted approach to the conservation of this species.…”
Section: Introductionmentioning
confidence: 99%